2019
DOI: 10.1039/c9ob00432g
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-catalyzed regiospecific (3 + 2) cyclization of 3-nitroindoles with allene esters

Abstract: The title reaction has been established to construct indole-fused five-membered rings in good yields (up to 86%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…80 Moreover, Shi's group also reported a similar CADA [3 + 2] cycloaddition of 3-nitroindole in the presence of commercially available chiral phosphines, which gave rise to cyclopentaindoline product in a moderate enantioselectivity. 82 Apart from the above mentioned three-atom building blocks, MBH carbonates could also serve as suitable threecarbon reaction partners in organo-CADA [3 + 2] annulations with 3-nitroindoles. In 2016, Chen and coworkers reported the first example of organo-CADA [3 + 2] annulation of 3-nitroindole 176b with isatin-derived MBH carbonate 186a under the catalysis of chiral DMAP-type Lewis base catalyst C41, generating cyclopentaindoline-based spirooxindole 187a in moderate enantioselectivity (Scheme 44a).…”
Section: Organo-cada Reactions Of 3-nitroindolesmentioning
confidence: 99%
“…80 Moreover, Shi's group also reported a similar CADA [3 + 2] cycloaddition of 3-nitroindole in the presence of commercially available chiral phosphines, which gave rise to cyclopentaindoline product in a moderate enantioselectivity. 82 Apart from the above mentioned three-atom building blocks, MBH carbonates could also serve as suitable threecarbon reaction partners in organo-CADA [3 + 2] annulations with 3-nitroindoles. In 2016, Chen and coworkers reported the first example of organo-CADA [3 + 2] annulation of 3-nitroindole 176b with isatin-derived MBH carbonate 186a under the catalysis of chiral DMAP-type Lewis base catalyst C41, generating cyclopentaindoline-based spirooxindole 187a in moderate enantioselectivity (Scheme 44a).…”
Section: Organo-cada Reactions Of 3-nitroindolesmentioning
confidence: 99%
“…In 2019, almost simultaneously, different publications reported the reactivity of allenoates 46 toward 3-nitro-indole derivatives 1 in the presence of phosphine organocatalysts, in the so-called Lu annulation, to generate fused cyclopentannulated indolines. 30,31,32,33,34,35 In the literature, Lu annulation processes have been shown to lead to two possible alpha and gamma regioisomers, the result of the two possible additions of the mesomeric 1,3-dipole A or B. Thus, the nucleophilic addition of the dipole to the position 2 of the electrophilic nitroindole can potentially lead to the formation of two regioisomers 47 and 48.…”
Section: Scheme 15mentioning
confidence: 99%
“…34,35 SPINOL-derived phoshine and amidophosphine derived from cyclohexyl-1,2-diamine could also be used as chiral organocatalysts in these reactions albeit with lower enantioselectivity. 32,33 Zhang and coll. showed that indoles 1 protected as carbamates were more reactive than their sulfonamidic analogues.…”
Section: Scheme 15mentioning
confidence: 99%
“…Different research groups have recently contributed to the phosphine‐catalyzed dearomative reaction of 3‐nitroindoles with allenoates, to yield the cyclopenta[ b ]indoline core through a formal [3+2] annulation process. [ 14 ] Shi [ 14a ] and Ye [ 14b ] have independently described the reaction of differently substituted N ‐protected 3‐nitroindoles 12 with diverse terminal allene esters 13a providing tricyclic adducts 14a as single diastereomers under similar reaction conditions (Scheme 3, path a). Both groups reported preliminary attempts towards the enantioselective version achieving moderate enantiomeric excesses (62 and 52 % ee).…”
Section: Intermolecular Reactionsmentioning
confidence: 99%
“…Both groups reported preliminary attempts towards the enantioselective version achieving moderate enantiomeric excesses (62 and 52 % ee). In a similar approach, de Paolis & Chataigner [ 14c ] reported the reaction with substituted allenoate 13b to generate cyclopenta [b ]indolines 14b exhibiting up to 3:1 dr (Scheme 3, path b). Enantiopure phosphines 15 and 16 have been respectively selected as chiral ligands by Zhang [ 14e ] and Yu [ 14f ] in two simultaneous approaches to the asymmetric formal [3+2] cycloaddition of 3‐nitroindoles 12 and allenoates 13a (Scheme 3, paths c and d).…”
Section: Intermolecular Reactionsmentioning
confidence: 99%